Aquatic copper-containing nitrite reductase gene (nirK) phylogeny and environmental distribution - Intrator, Naomi; Ward, Bess B. (Frontiers in Microbiology, 2025)
Nitrite reduction is an essential step in the oceanic Nitrogen cycle. Nitrite reductase genes, mainly nirS and nirK, are found in dozens of phyla, are often associated with denitrifiers, ammonia- and nitrite-oxidizing bacteria (AOB and NOB) as well as ammonia-oxidizing archaea (AOA). nirK is found throughout the ocean, including in oxygenated surface water as well as in oxygen minimum zones (OMZs). The diverse and complex evolutionary history of the nirK genes makes it challenging to study the population structure and distribution of nirK containing organisms in the environment. The organisms containing nirK play key roles in the global nitrogen cycle, including the loss of fixed N, and have the potential to influence nitrous oxide (N2O) emissions via multiple pathways. This study surveyed the phylogeny and environmental distribution of over 12,000 nirK genes, focusing on those originating from marine and aquatic sources. Sequences were clustered into OTUs based on DNA sequence identity and their phylogeny and environmental sources were examined. The distribution of the sequences showed habitat separation within taxonomic groups, i.e., the majority of the OTUs were associated with only one environmental source. Bacterial nirK is more diverse phylogenetically and has a wider distribution across environmental sources than archaeal nirK. Most of the bacterial sequences were obtained from marine sediments, but there was variation in the dominant environmental source across phyla and classes. Archaeal sequences demonstrated niche separation between phyla as sequences from the more phylogenetically diverse phylum, Euryarchaeota, were all isolated from hypersaline environments while Nitrososphaerota sequences came from a wider range of environmental sources. This study expands the known diversity of nirK genes and provides a clearer picture of how nirK organisms are distributed across diverse environments.